Clinical findings and surgical results of middle ear cholesteatoma behind an intact tympanic membrane in adults - Di Lella, Filippo; Bacciu, Andrea; Pasanisi, Enrico; Ruberto, Marco; D'Angelo, Giulia; Vincenti, Vincenzo (Acta Biomedica Atenei Parmensis, 2016)
Background and aim: Cholesteatoma usually arises in the middle ear by the formation of a retraction pocket or a tympanic membrane perforation. In some cases, cholesteatoma presents behind an intact tympanic membrane (ITMC) and the underlying mechanism of its development is controversial. The aim of this study was to describe clinical features, pathogenesis and surgical results in a series of adult patients affected by ITMC. Methods: We analyzed retrospectively 27 adult patients (age > 18 years) diagnosed with ITMC who underwent surgery between 1994 and 2013. We investigated the demographic data, presenting symptoms, otoscopic findings, disease location, surgical technique, postoperative complications and outcomes. Results: Diagnosis was made on the basis of a white mass seen through the tympanic membrane in 24 cases and on explorative surgery in the remaining 3 patients. In 16 cases cholesteatoma was related to an acquired cause, while in 11 ears a congenital origin was supposed. Hearing loss was the chief complaint and it was present in 19 (70.3%) subjects. Cholesteatoma was managed by purely endaural or retroauricular transcanal tympanoplasty in 12 cases, by planned staged canal wall up mastoidectomy in 10 cases (37%), by canal wall down mastoidectomy in 3 cases, and by modified Bondy technique in 2 cases. A recurrent cholesteatoma was observed in one ear; one patient experienced a postoperative profound sensorineural hearing loss. Conclusions: ITMC in adults may have both congenital and acquired origin. It may grow silently over many years and develops into a massive size before being detected. Each patient’s management should be tailored to clinical findings.